2010
DOI: 10.1111/j.1365-2214.2010.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

From financial hardship to child difficulties: main and moderating effects of perceived social support

Abstract: The study findings add to the now critical mass of data showing that parent-child health and well-being is inextricably linked with parental social support. While there is a burgeoning literature on parent training, far less research attention has been given to the development and evaluation of strategies to strengthen parents' social relationships. This is an important direction for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
140
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(161 citation statements)
references
References 66 publications
9
140
1
5
Order By: Relevance
“…Among the distal environmental influences, family income was not a significant contributor to increased number of questionable development problems at either infancy or early childhood, in contrast to the findings of previous research that reported family income predicted child outcomes (McConnell et al, 2011). Another study by Komro et al (2011) Among the other distal influences, caregiver's perception of the community as a negative child-rearing environment did not significantly predict questionable development of children less than 6 years old.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Among the distal environmental influences, family income was not a significant contributor to increased number of questionable development problems at either infancy or early childhood, in contrast to the findings of previous research that reported family income predicted child outcomes (McConnell et al, 2011). Another study by Komro et al (2011) Among the other distal influences, caregiver's perception of the community as a negative child-rearing environment did not significantly predict questionable development of children less than 6 years old.…”
Section: Discussioncontrasting
confidence: 55%
“…The longer children live in poverty, the more harmful its effect on their development, because their parents find it difficult to invest in children's learning (Komro et al). However, social and personal support may enhance both parent and family resilience in the face of difficult situations imposed by economic hardships (McConnell, Breitkreuz, & Savage, 2011). Higher levels of social and personal support have been linked to more effective parenting, less stress, and better child development outcomes (McConnell et al;Slykerman et al, 2005).…”
Section: Individual and Environmental Factors Influencing Questionablmentioning
confidence: 99%
“…Certain authors (e.g., Fearon et al 2006;Roisman and Fraley 2008) concur that these findings present a challenge to attachment and early parenting researchers who, until recently, have almost solely focused on identifying the antecedents of attachment security in variations in parenting quality assumed to be largely shared within families. These specific "causal factors'' could be identified (and then incorporated in genetically sensitive designs), for a start, through the study other theoretical models of parent-infant interactions than attachment theory; for instance, parental reflective functioning (e.g., Grienenberger et al 2005;Slade 2006), parenting styles (e.g., Cheah et al 2009), etc. On the other hand, as economic and psychosocial hardship and adversity may create considerable contextual stress and thus provide a negative background for early parent-infant interactions (Lee et al 2011;McConnell et al 2011;McLoyd 1998) which may be otherwise adaptive, "causal factors'' may be investigated more systematically within behavior-genetics designs in the form of psychosocial risk indicators (but for a few exceptions, see Asbury et al 2006;OuelletMorin et al 2008) such as family income, social support, familial history of substance abuse disorders or parents' education. Identification of specific mechanisms through which psychosocial adversity may affect early interactions with the infant (e.g., creation of a sense of hopelessness in the parent, parental anger/ frustration or depressive symptoms, lesser amount of time spent with the infant, fatigue) would also be necessary.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, teen parenthood (Morley et al 2011) and parent mental health (Atkinson et al 1999;Tarabulsy et al 2008) have been linked with adverse parenting behaviors. Contextual stressors, such as economic hardship and stressful life experiences (e.g., domestic violence) may also add to the burden of parenting (Lee et al 2011;McConnell et al 2011;McLoyd 1998). There is also empirical evidence to suggest that a child's early behavioral characteristics predict parental behaviors and perceptions (e.g., Caspi et al 2004;Jaffee et al 2004a;Kiff et al 2011;Putnam et al 2002), although there is disagreement about the importance and meaning of these potential "child effects" (Collins et al 2000;Dodge 1990).…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Investigators have used different conceptual models to understand how poverty affects child health and, specifically, asthma morbidity, often focusing on measures of socioeconomic status (SES), but detailed pathways and potential intervention points remain unclear. [10][11][12] Smoking and passive smoke exposure are both more common among socioeconomically disadvantaged populations 13 and associated with asthma morbidity. [14][15][16] Therefore, they may provide insight into how poverty "gets under the skin" of children with asthma.…”
mentioning
confidence: 99%